Methane‐Oxidizing Bacteria Communities Shift to Attenuate a Controlled Vadose Zone Methane Release. Issue 1 (29th November 2018) - Felice, Mark L.; Schmidt, Radomir; Peng, Juan; de Sieyes, Nicholas R.; Scow, Kate M.; Mackay, Douglas M.
Abstract : Core Ideas: The ecological niche of soil methane‐oxidizing bacteria (MOB) affects CH4 efflux. Results support application of the CSR model to MOB proposed by other researchers. The presence of MOB does not ensure complete CH4 oxidation. MOB require specific physical conditions to respond to CH4 inputs. Methane generated from small‐rate releases of ethanol‐blended fuels into the vadose zone potentially poses health and safety risks. Ubiquitous methane‐oxidizing bacteria (MOB) in soils can convert CH4 into CO2, potentially alleviating these risks. Understanding MOB ecology can help to better predict where subsurface CH4 production may pose health and safety risks and inform site management by identifying environmental conditions not conducive to CH4 mitigation. We established a densely monitored field site previously unexposed to high CH4 concentrations to allow the controlled release of CH4 into the vadose zone and monitoring of subsurface gas migration, surface efflux, and changes to MOB communities by quantitative polymerase chain reaction. During the initial stages of CH4 injection, soil conditions were very dry, and a large portion of the injected CH4 reached the ground surface as efflux. During this time, the composition of MOB remained similar to pre‐experimental conditions, with the Methylosinus group dominating. Following a period of rainfall and increased soil moisture conditions, efflux dropped, and only approximately 1% of injected CH4 was detected as efflux. The composition of the MOB community measured immediately following the drop in efflux had shifted so that near the injection point, the Methylobacter group of MOB was now dominant. This behavior followed the predictions of the competitor‐stress‐tolerator‐ruderal (CSR) ecological framework, which suggests that Methylosinus is a stress‐tolerating group while Methylobacter is a competitor group capable of degrading large amounts of CH4 but poorly suited for surviving stressful conditions.